Security Analysis on the Decentralized Energy Trading System Using Blockchain Technology - Rahmadika, Sandi; Ramdania, Diena Rauda; Harika, Maisevli (JOIN (Jurnal Online Informatika), 2018)
Blockchain turns both currencies and commodities into a digital form without relying on middleman which allows one person to trade with another include trading the renewable energy. Blockchain technology as a secure and low-cost platform to track the billions of eventual transactions in a distributed energy economy has attracted the attention of experts in various fields of science. The current form of centralized energy trading system is still suffering from security concerns, quality of service, and to name a few. A decentralized energy system using blockchain technology allows the parties to create a trading energy transaction via microgrid. The blockchain technology offers the promise of an immutable, single source of truth from multiple sources without a third-party involvement. In this paper, we describe, explore and analyze the prominent implementation of blockchain technology in the energy sector. Furthermore, we analyze the security issues and highlight the performance of several attacks that might be occurred in the proposed system.